2022
DOI: 10.26740/aluqud.v6n2.p289-303
|View full text |Cite
|
Sign up to set email alerts
|

Economic development on Madura Island through halal tourism: A business feasibility study

Abstract: The main objective of this research is to analyze the business feasibility of a halal tourism destination in Madura, exclusively Lon Malang Beach. The analysis includes technical, social economic, and financial feasibility study. The financial analytical method used in this study is Investment Feasibility Analysis includes Payback Period (PP), Net Present Value (NPV), and Benefit Cost Ratio (BCR). The investment feasibility analysis is used to determine the level of return-on-investment alternatives, assess in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Various studies have shown that implementing the right business strategy can have a positive and significant impact on company performance. Performance measurement in the context of SME business strategy can vary depending on the indicators used (Zakik et al, 2022). Choosing the right strategy will help SMEs achieve good performance and meet their business goals (Wardoyo, Rusdianti, and Purwantini, 2015).…”
Section: Business Strategymentioning
confidence: 99%
“…Various studies have shown that implementing the right business strategy can have a positive and significant impact on company performance. Performance measurement in the context of SME business strategy can vary depending on the indicators used (Zakik et al, 2022). Choosing the right strategy will help SMEs achieve good performance and meet their business goals (Wardoyo, Rusdianti, and Purwantini, 2015).…”
Section: Business Strategymentioning
confidence: 99%
“…However, ethical considerations regarding profit-sharing arrangements and regulatory frameworks governing Mudharabah transactions have also been explored, emphasizing the importance of transparency and effective oversight to ensure compliance with Sharia principles and enhance depositor trust (Ahmed & Ali, 2021;Rahman & Hassan, 2020). Mudharabah stands as a vital component of Islamic banking, promoting financial inclusion and economic development while necessitating ongoing scrutiny and refinement to address ethical and governance concerns (Zakik et al, 2022).…”
Section: Mudharabah (Islamic Deposit)mentioning
confidence: 99%
“…Junior baristas are still in the learning and training stage and work under the supervision of senior baristas or head baristas. In this case, to overcome these problems, a solution in the form of knowledge and skills is needed, with more and more knowledge gained, it will become a skill for each barista and become its specialty (Zakik et al, 2022).…”
Section: Introductionmentioning
confidence: 99%